2022
DOI: 10.1021/acs.orglett.2c01697
|View full text |Cite
|
Sign up to set email alerts
|

Benzotriazolium Salts: Emergent Readily Accessible Bench-Stable Lewis Acid Catalysts

Abstract: In this work, benzotriazolium salts have been introduced as efficient, readily accessible, bench-stable Lewis acid catalysts. Though these sorts of N-heterocyclic compounds have found wide applications as ionic liquids or electrolytes, their Lewis acid catalytic activity remained unexplored. Herein, their potential as Lewis acid catalysts was demonstrated in two prototypical allylic and Nazarov cyclization reactions, showing a matching reactivity and allowing low catalytic loadings (down to 0.5 mol %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Stephan et al extended these structures to five-membered cyclic alkyl amino nitrenium ions (B and C), 4 establishing their enhanced Lewis acidity compared to the corresponding triazolium species. All these findings opened a door to the emerging applications of these N-Lewis acids as non-innocent ligands, 5 partners in the frustrated Lewis pair chemistry, 6 and efficient catalysts for various transformations based on reduction, 6b,7 electrophilic cyclization, 8 and photoredox processes. 9 Of special interest are nitrenium salts based on sixmembered cyclic structures, such as naphthotriazinium cations D. We have previously demonstrated that species D have lower energy of the lowest unoccupied molecular orbital (LUMO) and are more acidic than their five-membered triazolium counterparts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephan et al extended these structures to five-membered cyclic alkyl amino nitrenium ions (B and C), 4 establishing their enhanced Lewis acidity compared to the corresponding triazolium species. All these findings opened a door to the emerging applications of these N-Lewis acids as non-innocent ligands, 5 partners in the frustrated Lewis pair chemistry, 6 and efficient catalysts for various transformations based on reduction, 6b,7 electrophilic cyclization, 8 and photoredox processes. 9 Of special interest are nitrenium salts based on sixmembered cyclic structures, such as naphthotriazinium cations D. We have previously demonstrated that species D have lower energy of the lowest unoccupied molecular orbital (LUMO) and are more acidic than their five-membered triazolium counterparts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Stephan et al extended these structures to five-membered cyclic alkyl amino nitrenium ions ( B and C ), establishing their enhanced Lewis acidity compared to the corresponding triazolium species. All these findings opened a door to the emerging applications of these N-Lewis acids as non-innocent ligands, partners in the frustrated Lewis pair chemistry, and efficient catalysts for various transformations based on reduction, , electrophilic cyclization, and photoredox processes …”
Section: Introductionmentioning
confidence: 99%
“…1A). 5 Despite the successes of these elegant ionic transformations utilizing NHNs, in terms of radical reactions, their catalytic ability is still underdeveloped. Recent years have seen great progress in the development of photoinduced charge transfer complex (CTC) catalysis as a way to implement radical processes to produce organic radicals.…”
Section: Introductionmentioning
confidence: 99%
“…This form demonstrates a nitrogen nonoctet character in these ions, which possess a relatively low LUMO and a free p-orbital on the central N-atom. These unique properties of NHNs allowed us and others to demonstrate that NHNs can act as nitrogen-based Lewis acids, [29][30][31][32][33] activators of strong bonds through frustrated Lewis pair chemistry, 30,34 catalytic Lewis acids for several reactions, [35][36][37][38] photocatalysts [39][40][41] and a platform for stable nitrogen-based radicals. 42,43 Exploring this Lewis acidity, we previously demonstrated that NHN 1 reacts with phenyllithium or n-butyllithium to furnish cyclic triazanes 2 (Scheme 2b).…”
Section: Introductionmentioning
confidence: 99%